Resistance switching of epitaxial VO2/Al2O3 heterostructure at room temperature induced by organic liquids - Mengmeng Yang; Yuanjun Yang; Bin Hong; Haoliang Huang; Sixia Hu; Yongqi Dong; Haibo Wang; Hao He; Jiyin Zhao; Xuguang Liu; Zhenlin Luo; Xiaoguang Li; et al. (AIP Advances, 2015)
We studied using organic liquids (cyclohexane, n-butanol, and ethylene glycol) to modulate the transport properties at room temperature of an epitaxial VO2 film on a VO2/Al2O3 heterostructure. The resistance of the VO2 film increased when coated with cyclohexane or n-butanol, with maximum changes of 31% and 3.8%, respectively. In contrast, it decreased when coated with ethylene glycol, with a maximum change of −7.7%. In all cases, the resistance recovered to its original value after removing the organic liquid. This organic-liquid-induced reversible resistance switching suggests that VO2 films can be used as organic molecular sensors.